(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In order to maintain and increase soil fertility in areas vacated from winter wheat, intercropping with cotton, corn, mung bean, peas, and rapeseed was studied, and their effect on winter wheat yield was studied. As a result of planting these intercropping crops, including plants that have a positive effect on soil fertility, such as mung bean, peas, and rapeseed, it was observed that winter wheat yield indicators also changed in a positive direction.